MITIGASI RISIKO BANJIR ROB RW 5 UTARA DESA WONOKERTO KULON KABUPATEN PEKALONGAN - Faris Gandi Muhammad; Endrawati Fatimah; Herika M. Taki (Jurnal Lingkungan dan Kota, 2021)
Tidal flood due to sea level rise often occurs in the Rukun Warga (local community unit) 5 Utara, Wonokerto Kulon located in costal area of Pekalongan Regency. The risk of tidal flooding is influenced by the physical vulnerability of the area. With the purpose to reduce the risk, it is necessary to carry out mitigation efforts by improving the physical conditions. This study aims to provide recommendation for mitigation efforts suitable for the area based on the levels of risk and physical vulnerability. To achieve the aim, the study identifies the level of hazard, the level of physical vulnerability and the level of risk by using Arc GIS spatial analysis and scoring techniques. The results show that around 44.38% of the area is classified as high-level tidal flood’s hazard. The level of hazards is identified based on height, frequency, and type of inundation. The physical vulnerability of this area is classified as in medium to high-level. The level of vulnerability is classified based on measured by the physical conditions which are buildings density, flooded road network, proximity to sea and rivers and land use. Based on the level of hazard and vulnerability, the tidal flood’s risk of the area is classified as in medium to high level. Recommended mitigation efforts to reduce the risk are conducting coastal zoning regulations, coastal preservation, mangrove conservation, development with adaptive spatial structure, coastal resettlement, and pond retention programs.